Respon Jarak Tanam dan Konsentrasi Pupuk Organik Cair Terhadap Pertumbuhan dan Produksi Tanaman Kale Nero Lacinato di Dataran Rendah - Alfin Indah Wahyuni; Mimik Umi Zuhro; Moch Su’ud Su’ud (G-Tech: Jurnal Teknologi Terapan, 2023)
This study aims to determine the response of plant spacing and concentration of liquid organic fertilizer on the growth and production of kale nero larinato (Brassica oleracea var. palmifolia) in the lowlands. This study used a split plot design consisting of two factors, namely: spacing with 3 levels and concentration of liquid organic fertilizer with 4 levels, and 3 replications. Parameters observed were plant height, number of leaves, root length, wet weight, and dry weight. The results showed that there was no significant effect on the two treatments of spacing and concentration of liquid organic fertilizer. The interaction of plant spacing treatment at a level of 20 x 25 cm and a concentration of liquid organic fertilizer at a level of 20 ml/l gave a significantly different effect on plant height at 48 DAP.